Rebel Mexico : student unrest and authoritarian political culture during the long sixties - Pensado, Jaime M., 1972- (Stanford University Press, 2013)
Pensado traces 'the rise' of Mexico's 'student problem' in the context of the long - and global - sixties (1956-c.1971). It is the first study to see the university as a physical space and a way of life that became a crucial point for the transformation of political and cultural values, with key ramifications for the country as a whole.